Geographical indications as a means of valorization of economic business - a chance for rural recovery - Lukinovic, Mario; Opacic, Ana; milojevic, ivan (Sociološki pregled, 2022)
Preservation of the characteristics of agricultural and food products is directly correlated with the system of geographical indications. Today, in more than 150 countries around the world, geographical indications are in the service of guaranteeing quality, origin, method of production, often tradition and, finally, product safety. The authors point out the changes in consumer behaviour, the change in the propensity to consume products that are differentiated on the market by different forms of marking and certification, and the willingness to pay for the same products at premium prices. Additional labels have imposed themselves as the main means of valorizing products on the market. The authors point out the potential of Serbian agriculture and give recommendations to the legislator, but also to other competent institutions, in order to improve position of the overall national economy. Ecological, agriculture, based on the principles of non-GMO impurities, with a clear commitment to the integral principles of land cultivation represents the greatest potential of our country. Additional state measures that would support better education and improvement of the position of farmers, with careful strategic planning of agriculture on the already mentioned principles, would make it an accelerator of the overall economic development. Geographical indications as well as standardization and certification must be an indispensable tool along the way.
Keywords: geographical indications; standardization; village recovery